2020
DOI: 10.1371/journal.pone.0242713
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and species identification of Plasmodium spp. infection in adults in the Democratic Republic of Congo: A population-based study

Abstract: Background In efforts to control malaria infection, the Democratic Republic of Congo has implemented several strategies. Studies assessing their efficiency mainly involved at-risk groups, especially children under five years of age. This study aimed to determine the prevalence and identify the risk factors associated with Plasmodium spp. infection. Methods From October 2014 to March 2015, individuals aged at least 15 years were selected randomly and enrolled in a cross-sectional study conducted throughout th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Similar prevalences were observed among symptomatic individuals. Prevalences generally align with previous estimates of non-falciparum infections in the DRC derived from cross-sectional studies 14,[16][17][18][19][20][21][22]41 . Infection prevalences were stable across the 34-month follow-up, differing from recent studies in neighboring countries which have detected increases in P. malariae and P. ovale infection prevalence over time, particularly as P. falciparum prevalences have started to decline 3,4,6 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar prevalences were observed among symptomatic individuals. Prevalences generally align with previous estimates of non-falciparum infections in the DRC derived from cross-sectional studies 14,[16][17][18][19][20][21][22]41 . Infection prevalences were stable across the 34-month follow-up, differing from recent studies in neighboring countries which have detected increases in P. malariae and P. ovale infection prevalence over time, particularly as P. falciparum prevalences have started to decline 3,4,6 .…”
Section: Discussionsupporting
confidence: 81%
“…have been documented at low-level prevalences in the DRC 8,[14][15][16] ; however, their epidemiology and clinical impact remains poorly understood. Existing non-falciparum prevalence estimates were largely derived from cross-sectional studies, limiting risk assessment, or focused on a singular age group or symptomatic status, which restricts broader generalizability 14,[16][17][18][19][20][21][22] . The absence of reliable field diagnostics for these less-common infections complicates surveillance efforts and case management.…”
Section: Introductionmentioning
confidence: 99%
“…Kiyonga et al, 2020), and might be from degradation of extracted DNA due to poor storage conditions and the activity of DNase that digests DNA molecules. This observation contradicts those ofMbuyi et al (2014) who reported that P. falciparum DNA was amplified in all the samples shown to be infected by microscopy examination.…”
mentioning
confidence: 99%